Fatal cases after Omicron BA.1 and BA.2 infection: Results of an autopsy study. (March 2023) - Märkl, Bruno; Dintner, Sebastian; Schaller, Tina; Sipos, Eva; Kling, Elisabeth; Miller, Silvia; Farfán López, Francisco; Grochowski, Przemyslaw; Reitsam, Nic; Waidhauser, Johanna; Hirschbühl, Klaus; Spring, Oliver; et al.
Highlights: Diffuse alveolar damage occurs after Omicron BA.1/2 infections. Only a third of fatal cases after Omicron BA.1/2 infection were caused by COVID. No factors discriminating between COVID and non-COVID deaths have been identified. A high rate of severe acute pneumonia has been observed. Abstract: Objectives: Omicron lineages BA.1/2 are considered to cause mild clinical courses. Nevertheless, fatal cases after those infections are recognized but little is known about risk factors. Methods: A total of 23 full and three partial autopsies in deceased with known Omicron BA.1/2 infections have been consecutively performed. The investigations included histology, blood analyses, and molecular virus detection. Results: COVID-19-associated diffuse alveolar damage was found in only eight cases (31%). This rate is significantly lower compared with previous studies, including non-Omicron variants, where rates between 69% and 92% were observed. Neither vaccination nor known risk factors were significantly associated with a direct cause of death by COVID-19. Only those patients who were admitted to the clinic because of COVID-19 but not for other reasons had a significant association with a direct COVID-19 –caused death ( P >0.001). Conclusion: Diffuse alveolar damage still occurred in the Omicron BA.1/BA.2 era but at a considerably lower frequency than seen with previous variants of concern. None of the known risk factors discriminated the cases with COVID-19-caused death from those that died because of a different disease. Therefore, the host's genomics might play a key role in this regard. Further studies should elucidate the existence of such a genomic risk factor.